Tradisi Metuakan sebagai Sarana Integrasi Sosial dalam Pandangan Warga Puri Agung Karangasem - Aliffiati, Aliffiati; Wedasantara, Ida Bagus Oka (Jurnal Sosiologi Andalas, 2025)
Tuak (palm wine) is a traditional alcoholic drink made in the Indonesian archipelago. It is made form sap water of coconut palm, and aren palm plants. For the Balinese people, Tuak is not just a drink but also a complement to offerings. Metuakan is a way of serving and enjoying Tuak . It is part of the culinary tradition of the people born from the habit of drinking palm wine. Government regulation legalise consuprion of Tuak. This study is to find the views of Puri Agung Karangasem regarding the metuakan tradition for social integration. The concept of social integration is a theoretical framework for this article. This research applies ethnographic (qualitative) methods through observation, interviews, and literature studies. The collected research data were analyzed by interpretation. Research results show that metuakan tradition for puri relatives is not limited to entertainment, but rather a means to familiarize interaction and integration between the puri society and between the puri family and the parekan. The existence of the puri is very supportive in maintaining and developing the metuakan tradition as part of the people's culinary traditions and cultural resources, which can prosper society in the end.